1993
DOI: 10.1111/j.1476-5381.1993.tb13828.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral blood flow and cerebrovascular reactivity after inhibition of nitric oxide synthesis in conscious goats

Abstract: 1 The role of nitric oxide in the cerebral circulation under basal conditions and after vasodilator stimulation was studied in instrumented, conscious goats, by examining the action of inhibiting endogenous nitric oxide production with N0-nitro-L-arginine methyl ester (L-NAME). 2 In 6 unanaesthetized goats, blood flow to one brain hemisphere (electromagnetically measured), systemic arterial blood pressure and heart rate were continuously recorded. L-NAME (35 mg kg-' by i.v. bolus) decreased resting cerebral bl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…25,35) Consistent with previous reports in the rat and other species, 5,6,25) we also found that L-NMMA induced secondary bradycardia of approximately 30 bpm which is known to involve autonomic reflexes as it is abolished, and the associated pressor response potentiated, by baroreceptor deafferentiation. 35) In the present study, these systemic responses to L-NMMA were attenuated by pre-and post-administration of L-arginine, and changes in the P-Q characteristics of the ECA territory induced by L-NMMA were reversed by post-administration of L-arginine.…”
Section: Discussionsupporting
confidence: 91%
“…25,35) Consistent with previous reports in the rat and other species, 5,6,25) we also found that L-NMMA induced secondary bradycardia of approximately 30 bpm which is known to involve autonomic reflexes as it is abolished, and the associated pressor response potentiated, by baroreceptor deafferentiation. 35) In the present study, these systemic responses to L-NMMA were attenuated by pre-and post-administration of L-arginine, and changes in the P-Q characteristics of the ECA territory induced by L-NMMA were reversed by post-administration of L-arginine.…”
Section: Discussionsupporting
confidence: 91%
“…[23][24][25][26][27] It is postulated that vasoconstriction is partially mediated by the suppression of NO, synthesized from L-arginine in the perivascular nerve terminals innervating the arteries that irrigate the cerebrum, as treatment with a ganglion blocker can suppress vasoconstriction or cause a decrease in blood flow. 21 We therefore conclude that in the arteries irrigating the cerebrum, cerebellum and brain stem, constrictions induced by intravenous L-NA may be partially associated with the suppression of nitrergic function.…”
Section: Discussionmentioning
confidence: 99%
“…[1][2][3][4][5][6] Although this experimental NOdeficient hypertension at first was attributed solely to inhibition of endothelium-dependent vasodilation, 1,7 there is increasing evidence of an important sympathetic neural component. 5,6,8 -12 The concept is that neuronally produced NO is part of the signal transduction pathway involved in the restraint of brainstem sympathetic vasomotor outflow and that inhibition of such restraint leads to neurogenic hypertension.…”
Section: P Harmacological Inhibitors Of Nitric Oxide (No) Synthesis mentioning
confidence: 99%